2009
DOI: 10.1016/j.ab.2008.11.042
|View full text |Cite
|
Sign up to set email alerts
|

A tetracycline repressor-based mammalian two-hybrid system to detect protein–protein interactions in vivo

Abstract: A mammalian two-hybrid system (termed as trM2H) was developed to detect protein-protein interactions in vivo, based on the reconstitution of the functions the of tetracycline repressor (TetR). The system is sensitive enough to detect protein-protein interactions with K(d) up to 55microM in mammalian cells, and the system can be regulated by small molecules. This system can be used as an efficient genetic selection system to map protein-protein interactions in mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…We first tested the interaction of TOP1 and BOT1 to the Abl SH3 domain in vivo using the established tetracycline repressor-based mammalian two hybrid system (trM2H) that is sensitive to weak interactions [20]. This system takes advantages of the dimeric TetR transcription regulator which binds to the Tet-responsive element (TRE) sequence at upstream of reporter gene (AcGFP) to induce its expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first tested the interaction of TOP1 and BOT1 to the Abl SH3 domain in vivo using the established tetracycline repressor-based mammalian two hybrid system (trM2H) that is sensitive to weak interactions [20]. This system takes advantages of the dimeric TetR transcription regulator which binds to the Tet-responsive element (TRE) sequence at upstream of reporter gene (AcGFP) to induce its expression.…”
Section: Resultsmentioning
confidence: 99%
“…Restriction enzyme sites AgeI and KpnI were introduced into pTetOff previously to afford pTOAgeIKpnI [20]. The coding sequences for TOP1 and BOT1 were purchased as complementary oligonucleotides (Invitrogen) and annealed.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that the C-terminal catalytic domain of SrtA selectively forms a homo-dimer in vitro and in E. coli. [18][19][20][21] Herein, we demonstrate that SrtA also forms homo-dimer on the membrane of S. aureus and such dimerization mediates SrtA's activities on the cell membrane, suggesting that the dimerization of SrtA is one of the mechanisms to globally coordinate the cell surface decoration on S. aureus.…”
Section: Introductionmentioning
confidence: 95%
“…Another variation on the two-hybrid theme in mammalian cells is the tetracycline repressor-based system, trM2H (638). In trM2H, hybrids are composed of three functional parts: DNA binding of two tetracycline repressor (TetR) fragments is restored upon bait-prey interaction, leading to activation of transcription by the VP16 AD domain.…”
Section: Mammalian Genetic Protein-protein Interaction Systemsmentioning
confidence: 99%